Analisis Puisi “Aku” Karya Chairil Anwar: Pendekatan Objektif dan Pragmatik - Monica Syafitri; Gusti Yarmi; Saifur Rohman (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
Poetry is one of the literary genres that contains aesthetic values and reflects the author's thoughts, emotions, and perspectives through language. This study aims to analyze the poem “Aku” by Chairil Anwar using objective and pragmatic approaches. The objective approach focuses on intrinsic elements of the poem, including theme, imagery, rhyme, typography, figurative language, tone, feeling, and message, while the pragmatic approach examines the impact and meaning of the poem from the readers’ perspective and its social context. This study employed a qualitative descriptive method with document analysis techniques. The primary data source was the poem “Aku” by Chairil Anwar. The findings indicate that the poem portrays themes of individualism, freedom, struggle, and resilience through expressive diction and strong imagery. The objective analysis reveals that the poem is structured by various literary elements that strengthen its aesthetic quality and meaning. Meanwhile, the pragmatic analysis shows that the poem encourages readers to reflect on human existence, independence, courage, and the search for meaning in life. The study implies that literary appreciation through objective and pragmatic approaches can enrich readers’ understanding of literary works and foster critical interpretation skills in literature learning.